Development of Community-Based Mental Health Interventions in The Philippines: An Ecological Perspective - Hechanova, Ma. Regina M. (Psychological Research on Urban Society, 2019)
Although urbanization is linked to modernization and economic growth, it is also associated with overcrowding, population density, poverty, inadequate social services, and violence, all of which put the urban poor at risk of environmental health problems and other dangers. Moreover, experiences of environmental and psychological adversity increase vulnerability to mental health disorders. Unfortunately, in low resource countries, mental health treatment is largely inaccessible to the poor. This paper describes the challenges in the development and implementation of community-based mental health interventions in the Philippines. It summarizes the internal and external resilience factors and vulnerabilities of clients. It also highlights the key drivers and barriers to establishing community-based mental health interventions in the Philippines.